2022
DOI: 10.1038/s41598-022-14414-4
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling mitochondrial piRNAs in mouse embryonic gonadal cells

Abstract: Although mitochondria are widely studied organelles, the recent interest in the role of mitochondrial small noncoding RNAs (sncRNAs), miRNAs, and more recently, piRNAs, is providing new functional perspectives in germ cell development and differentiation. piRNAs (PIWI-interacting RNAs) are single-stranded sncRNAs of mostly about 20–35 nucleotides, generated from the processing of pre-piRNAs. We leverage next-generation sequencing data obtained from mouse primordial germ cells and somatic cells purified from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 104 publications
2
5
0
Order By: Relevance
“…piRNAs are largely present in the mitochondria of testis, representing the most predominant population of small RNAs ( Fig 2 ); their finding into mitochondria of testis is consistent with bioinformatic analyses on smallRNAseq libraries from primordial germ cells and spermatozoa of male mice [ 21 , 41 ]. Surprisingly, here piRNAs were also detected in the mitochondria of the other tissues, representing a novelty in the current knowledge ( S1 Table ).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…piRNAs are largely present in the mitochondria of testis, representing the most predominant population of small RNAs ( Fig 2 ); their finding into mitochondria of testis is consistent with bioinformatic analyses on smallRNAseq libraries from primordial germ cells and spermatozoa of male mice [ 21 , 41 ]. Surprisingly, here piRNAs were also detected in the mitochondria of the other tissues, representing a novelty in the current knowledge ( S1 Table ).…”
Section: Resultssupporting
confidence: 78%
“…Mitochondria were purified as described in Material and Methods section, and smallRNA sequencing experiments were performed on extracted RNAs ( ; their finding into mitochondria of testis is consistent with bioinformatic analyses on smallRNAseq libraries from primordial germ cells and spermatozoa of male mice [21,41]. Surprisingly, here piRNAs were also detected in the mitochondria of the…”
Section: Plos Onementioning
confidence: 54%
See 2 more Smart Citations
“…Among these candidates, piR-mmu-7,456,245, which showed relatively high expression in all types of cells, was detected to localize in mitochondria [ 21 ]. This research group also identified piRNAs by RNA-seq, which might be generated from the mitochondrial genome—or mitochondrial counterparts in the nuclear genome in mouse embryonic gonadal cells—indicating a potential piRNA-mediated communication between mitochondria and the nucleus [ 22 ]. Overall, the research on mitochondrial piRNAs is still superficial.…”
Section: Mitochondrial Piwi-interacting Rnasmentioning
confidence: 99%